Building an Index System for Evaluating the Motor Health of Preschool-aged Children from the Perspective of Disciplinary Intersections: A Delphi Study - Du, Dongxu; Choosakul, Chairat (Physical Education Theory and Methodology, 2025)
Background. Sports health and the future of preschool children are urgent problems. However, a comprehensive and scientific evaluation index system (EIS) for assessing their sports health is lacking. Objectives. The study aimed to elaborate an EIS for preschool children’s motor health based on interdisciplinary subjects to solve the growth dilemma faced by children during their development. Materials and methods. Sixteen interdisciplinary experts who have been engaged in sports and health education for more than 15 years participated in a Delphi study. They used a 5-point Likert scale twice to assess the importance of preset indicators and provided feedback to modify and allocate items to the EIS. Results. After two rounds of expert consultation, a consensus was reached on the EIS, which included 6 primary and 26 secondary indicators. The coefficients for experts’ familiarity (As), judgment (Ai), and authority (Aa) were all >0.7. The coefficients for opinion coordination (ω) were >0.7. The arithmetic mean (Mean) of the recognition and operability scores was ≧4, and the coefficients of variation (CV) were all <0.25. The harmonization coefficient (ω) for the primary indicators was 0.803, and the harmonization coefficient (ω) for the secondary indicators was 0.758 (all > 0.75). Conclusions. Accurate, reliable and scientific data were collected to develop an EIS in order to address the challenges of assessing children’s motor health. The findings can serve as a reference for future instruction on preschoolers’ motor health.